2007
DOI: 10.1590/s0100-29452007000200017
|View full text |Cite
|
Sign up to set email alerts
|

Preferência alimentar de Dione juno juno (CRAMER, 1779) (Lepidoptera: Nymphalidae) por genótipos de maracujazeiro

Abstract: MARINA ROBLES ANGELINI2 & ARLINDO LEAL BOIÇA JÚNIOR 3 RESUMO -O presente trabalho teve por objetivo determinar o efeito de genótipos de maracujazeiro quanto à atratividade e à não-preferência para alimentação de lagartas de Dione juno juno, em diferentes idades, através de testes com e sem chance de escolha. Os experimentos foram conduzidos no Departamento de Fitossanidade da FCAV/UNESP de Jaboticabal-SP, sob condições ambientais controladas (T=26=±=1°C=U.=R.= 60 ± 10% e fotofase = 14 horas), utilizando-se dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Angelini and Boiça Júnior [5] working with ten sour passion fruit genotypes to evaluate the food preference of D. juno juno caterpillars, found that no significant difference between in genotypes in relation to dry mass consumption by caterpillars aged ten days in the test with a chance of choice. The gregarious feeding of herbivorous insects assists in the exploration of its host plant.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Angelini and Boiça Júnior [5] working with ten sour passion fruit genotypes to evaluate the food preference of D. juno juno caterpillars, found that no significant difference between in genotypes in relation to dry mass consumption by caterpillars aged ten days in the test with a chance of choice. The gregarious feeding of herbivorous insects assists in the exploration of its host plant.…”
Section: Resultsmentioning
confidence: 99%
“…Pests associated with sour passion fruit can cause economic damages, as they promote reduction in fruit production and, in extreme cases, cause the death of plants. In this way, sour passion fruit breeding programs aim to improve morphological, physiological and agronomic characteristics that promote greater productivity increase, fruit quality improvement and resistant or pest tolerant genotypes [5,6,7].…”
Section: Introductionmentioning
confidence: 99%